Faktor-Faktor yang mempengaruhi Pendapatan Petani Garam di Desa Wewaria, Kecamatan Wewaria, Kabupaten Ende - Kaki, Fransiskus; Nona, Reyna Virginia; Sedho , Yuliana (Program Studi Ekonomi Pembangunan Universitas Flores, 2022)
ABSTRACT This study aims to determine the factors that affect the income of saltfarmers in Wewaria Village, Wewaria District, Ende Regency. The type ofresearch used is a quantitative approach to see if there is an influence of capital,labor, land area and selling prices on the income of salt farmers. This researchdata was obtained from questionnaires and observations as well as directinterviews with related parties, namely salt farmers. The analytical method used to test the correctness of this hypothesis is a multiple linear regression model in the form of the SPSS Version 24 program. The results showed that first, capital had a positive and significant effect on the income of salt farmers, where the value of twas calculated > ttable (2.227 > 1.662). Second, labor has a positive and significant effect on the income of salt farmersbecause the value of tis calculated > ttable (2.148 > 1.662). Third, land area has apositive and significant effect on the income of salt farmers, because the value oftis calculated > ttable (2.161 > 1.662). Fourth, the selling price has a positive andsignificant effect on the income of salt farmers because the value of tis calculated >ttable (2,930 > 1,662). The five capital, labor, land area, and selling pricesimultaneously have a positive and significant effect on the income of saltfarmers, with Fcalculated values > Ftables (35,723 > 2.48). The six selling prices are themost dominant factors affecting the income of salt farmers in Wewaria Village,Wewaria District, Ende Regency.